Hurry and the monarch - Ó Flatharta, Antoine (Knopf : Distributed by Random House, 2005)
Hurry the tortoise befriends a monarch butterfly when she stops in his garden in Wichita Falls, Texas, during her migration from Canada to Mexico. Includes facts about monarch butterflies.